Establishing Scientific Discourse in Classroom Interaction Teacher Students' Orientation to Mundane Versus Technical Talk in the School Subject Norwegian - Skovholt, Karianne (Scandinavian journal of educational research, 2018)
This article reports a case study on classroom interaction in teacher education in Norway. It addresses how teacher students in the school subject Norwegian constitute scientific talk in a student-led discussion. First, the analysis reveals tension in the classroom conversation between mundane talk-that is, where students make claims with reference to their personal epistemic domain-and scientific talk-that is, where students make claims with reference to a shared scientific epistemic domain. Then, the analysis identifies specific interactional resources (reproach, embedded correction, formulation, and recontextualization) that the students use to regulate and bridge the 2 levels of discourse. Finally, the article provides insights into how scientific discourse is collaboratively established through conversational turns and considers how teacher education might use these findings for communication-skill training.